2000
DOI: 10.1177/107834580000700102
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about HSV and HPV and Sexual Behavior Among Incarcerated Adolescent Women

Abstract: Using the Commonsense Model (Skelton & Croyle, 1991), this study examines incarcerated adolescent females' beliefs about the human papillomavirus (HPV) and herpes simplex virus (HSV) infections and the relationship between their beliefs and safer sexual practices. Participants included 54 volunteers of various ethnicities, whose average age was 15.9 years. They completed a questionnaire focusing on their beliefs about HPV and HSV and frequency of safer sexual behaviors. Beliefs about the two infections were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In previous research, STD illness representations (HPV, HSV, and HIV) were consistent with the dimensions of the CSM (Keller, 1993; Sacajiu et al, 2007; von Sadovszky et al, 2000). However, these studies were either qualitative or used representational instruments that had not been subject to statistical analyses to determine the structure of STD representations.…”
Section: Common Sense Modelsupporting
confidence: 72%
See 2 more Smart Citations
“…In previous research, STD illness representations (HPV, HSV, and HIV) were consistent with the dimensions of the CSM (Keller, 1993; Sacajiu et al, 2007; von Sadovszky et al, 2000). However, these studies were either qualitative or used representational instruments that had not been subject to statistical analyses to determine the structure of STD representations.…”
Section: Common Sense Modelsupporting
confidence: 72%
“…The CSM posits that individuals have beliefs about illnesses, called illness representations, and these beliefs, regardless of whether or not they are medically accurate, guide subsequent health behaviors. For example, there is evidence that accurate HPV illness representations are associated with safer sex practices (von Sadovszky, Carlson‐Dakes, & Keller, 2000). According to the CSM, illness representations have five dimensions: cause, identity, timeline, consequences, and cure/control.…”
Section: Common Sense Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…PHNs and other care providers should consider how misconceptions may negatively influence behavior and perpetuate STIs. This is critical as previous research has identified that the accuracy of STI representations is associated with safer sexual behavior (von Sadovszky, Carlson‐Dakes, & Keller, 2000). To illustrate this point, recall that all three focus groups mentioned that some young people believe that STIs cannot be transmitted via oral sex.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not specifically explore variation in provider perceptions by type of STI. Given that there is evidence that representations can vary by infection type (von Sadovszky et al, 2000), future investigations are necessary to comprehensively explore provider perceptions of patients' representations about specific types of STI.…”
Section: Discussionmentioning
confidence: 99%